TRACK GAUGE STABILITY UNDER EFFECT OF SLEEPER THERMAL EXPANSION - Vít Lojda; Hana Krejčiříková (Acta Polytechnica, 2019)
Railway sleepers are traditionally made of hardwood, pre-stressed concrete or steel. However, emerging advanced materials, including polymers or composites, are investigated for a possible employment in the sleeper production. The main function of sleepers is to distribute forces they carry onto the trackbed, to support rails and keep the spacing between them, called the track gauge. The operating tolerance of the track gauge is critical for safety and is set by regulations. Generally, it is advisable to keep the track gauge deviation, as well as the sleeper length deviation influencing it, as low as reasonably practicable. In this article, the recommended limit values of the thermal expansion coefficient characterizing possible sleeper length deviation were evaluated. The recommendation considered allowed track gauge tolerance and the experimentally determined temperatures of a sleeper measured in the trackbed for a year. In addition, thermal expansion of a selected polymer in laboratory conditions was determined, representing an alternative material for the sleeper production. Consequently, it was compared with the limit and conservatively used materials. Furthermore, the same tested polymer, but utilizing chopped glass fibres to reduce the thermal expansion of the polymer, was also tested. Results show a positive impact of the glass reinforcement on the thermal expansion coefficient. The applicability of the selected polymer in the railway sleeper production from the perspective of the thermal expansion was discussed in the paper.